Efficacy of bortezomib, cyclophosphamide and dexamethasone in cardiac AL amyloidosis. Issue 10 (20th October 2022) - Brennan, Xavier; Withers, Barbara; Jabbour, Andrew; Milliken, Sam; Kotlyar, Eugene; Fay, Keith; Ma, David; Muthiah, Kavitha; Hamad, Nada; Dodds, Anthony; Bart, Nikki; Keogh, Anne; et al.
Abstract: Cardiac light chain (AL) amyloidosis is a condition with a very poor prognosis. We report a retrospective analysis comparing the traditional melphalan and dexamethasone protocol with cyclophosphamide, bortezomib and dexamethasone in late‐stage cardiac AL amyloidosis. The primary end points were overall survival and haematological response. Both regimens provided meaningful responses in this difficult to treat patient group.